Dealing with frustration: a grounded theory study of CVE practitioners - Lehane, Orla (International journal of conflict and violence, 2018)
Understanding how best to proceed in the prevention of violent extremism is a significant concern for researchers and practitioners. This paper draws on interviews with thirty ‘countering violent extremism’ (CVE) practitioners, using a grounded theory approach focusing on those working at grassroots level, to highlight the way in which these individuals are mining their own personal experiences in their approaches to this work. Driven by a sense of frustration with the ‘accepted wisdom’, this involves drawing on personal skills and experiences to establish themselves as credible actors, thereby carving a space for themselves within a growing CVE industry. Moving beyond anecdotal evidence using grounded theory, this paper offers a systematic analysis of the experiences of these frontline practitioners. In considering what it is that practitioners are doing, and the context that pushes them to adopt this approach, this research offers significant insights into what is actually happening in the area of practice, contributing to understandings of the prevention landscape as a whole. This paper highlights the tensions between actors operating at different levels within the CVE sphere, with discrepancies in resources and power playing a central role.